Parental Involvement and Learners’ Achievement: Basis for Action Plan - Judith D. Bersabal; Wenie L. Nahial (Future Science / FSH-PH Publications, 2026)
Parental involvement has been noted to have played a vital role in the education of the children in the family. On this regard, the study aimed to determine the parental involvement of the respondents and its relationship to the academic achievement of the respondents’ learners or pupils. Following established research protocols, 88 parents of kindergarten pupils voluntarily participated as respondents in the study. A quantitative descriptive research design was employed, supplemented by a survey questionnaire and a casual interview, to address the study's inquiries. Appropriate statistical tools were used in the analysis of data. The results showed that most respondents were female. The majority of them were young adults from poor and medium-sized families who failed to complete the mandatory basic education offered free by the government. Parental involvement in terms of bonding and bridging was perceived to a high extent, while linking was perceived at a moderate extent. Perceptions of parental involvement focused on the support coming from within the family, as well as that from outside, which can provide an avenue or opportunity for pupils to gain more experiences and grow through social affiliation. Pupils’ achievement was at a very satisfactory performance level. The relationship between parental involvement and pupils’ achievement was found to be negligible, negative, and non-significant. Parental involvement, even if at high extent, does not translate directly to the academic performance of the pupils. Other factors were not accounted for that may have influenced the pupil’s achievement.